Response of growth and salinity tolerance of Nauclea orientalis L. seedlings to arbuscular mycorrhizal fungi - Faisal Danu Tuheteru; Husna Husna; Asrianti Arif; Basrudin Basrudin; Albasri Albasri; Yudhi Renggaala; Wiwin Rahmawati Nurdin; Miranda Hadiyanti Hadijah2; Ikraeni Safitri (Journal of Tropical Mycorrhiza, 2022)
The purpose of this study was to determine the effectiveness of AMF types on the increasing growth of Lonkida (Nauclea orientalis L.) plants under salinity stress conditions. This study was carried out in the plastic home of the Indonesian Mycorrhizal Association Southeast Sulawesi branch, Kendari City and Forestry Laboratory, for five months, march - July 2019. This study used a Factorial Completely Randomized Design consisting of 3 replications and three plant units. The first factor included treatment without AMF, Acaulospora sp1. and Clorideglomus etunicatum. The second factor includes Salinity 0 mM, 50 mM, 100 mM, 150 mM and 200 mM. The results showed that the interaction of AMF and salinity was not effective in increasing plant growth. Inoculation of AMF type C. etunicatum can increase height, plant dry weight, root shoot ratio, seed quality index, and root colonization. N. orientalis has a high dependence on arbuscular mycorrhizal fungi. Giving 0 mM salinity increases height, diameter, number of leaves, plant dry weight, and seed quality index